The Neotropical cleptoparasitic bee Mesocheira bicolor (Hymenoptera: Apidae: Ericrocidini) in Argentina - Torretta, Juan Pablo (2024)
Mesocheira bicolor (Fabricius) is a cleptoparasite bee, widely distributed in the New World from Mexico to northern Argentina. In Argentina, this species is only documented from Formosa. In this contribution, we report new records of males and females reared from trap nests obtained from different studies about nesting biology of solitary bees in pre-existing cavities in several Argentinian provinces. Also, we studied material from Argentinean research collections, and we searched for occurrence data in the Global Biodiversity Information Facility. Adults of M. bicolor were reared from nests of Centris(Hemisiella) tarsata and C. (Hemisiella) nigriventris Burmeister. Here, we reported eight new provincial records that widely increase the geographical distribution of this species in Argentina, expanding its austral most distribution record by more than 1,000 km.